Psychoacoustics: Facts and Models - Zwicker, Eberhard; Fastl, Hugo (Springer Series in Information Sciences, 2013)
Psychoacoustics - Facts and Models represents a comprehensive collection of data describing the processing of sound by the human hearing system. It includes quantitative relations between sound stimuli and auditory perception in terms of hearing sensations. In addition, quantitative psychoacoustic models of hearing sensations are given. The monograph contains a unique collection of data on the human hearing system as a receiver of acoustic information as well as many examples of the practical application of the results of basic research in fields such as audiology, noise evaluation, and sound engineering. Many helpful hints for the solution of practical problems will be of particular benefit to engineers, and the book as a whole should serve as an important benchmark in the field of psychoacoustics. The treatment given in this second edition has been thoroughly updated with recent results.